A lactate related signature for predicting prognosis and tumor microenvironment in lung adenocarcinoma - Ying Wang; Huiting Li; Chao Chen; Hui Yu; Lichao Xu (Discover Oncology)
Abstract Background Lactate plays a critical role in tumor development, metastasis, drug resistance, and regulation of tumor microenvironment. This study aimed to develop a prognostic signature for lung adenocarcinoma (LUAD) based on lactate-related genes (LRGs). Methods We initially performed univariate Cox regression analysis on 269 cases of LRGs in TCGA- LUAD cohort to determine LRGs related to overall survival (OS). Fourteen LRGs were used to construct a prognostic risk model and verified in three external cohorts (GSE31210, GSE68465, and GSE30219). The relationship between risk model and immune cell infiltration, as well as drug sensitivity was explored. The expression of 14 key genes in lung cancer cell lines (A549, NCI-H2009, and NCI-H1975) and normal bronchial epithelial cell line (BEAS-2B) was detected by qRT-PCR. Results A 14-LRG prognosis signature was constructed. Patients in the high-risk group had significant worse OS compared to those in the low-risk group (HR = 2.33; 95%CI, 1.72–3.14; P < 0.0001). Three independent external verification cohorts were used to verify our results, and consistent results were observed in them. There are significant differences in the infiltration of seven kinds of immune cells between high-risk and low-risk patients with LUAD. Low-risk patients responded well to carboplatin and paclitaxel, whereas high-risk patients were more sensitive to docetaxel (P < 0.05). Additionally, qRT-PCR confirmed that the expression of prognostic genes was basically consistent with the results of bioinformatics analysis. Conclusion We successfully developed and validated a 14-LRG prognostic signature for LUAD, which was associated with immune status and drug resistance.